Effect of Berberis vulgaris L. root extract on ifosfamide-induced in vivo toxicity and in vitro cytotoxicity - Shazia Ilyas (Nature Portfolio, 2021)
Abstract Ifosfamide is a widely used chemotherapeutic agent having broad-spectrum efficacy against several tumors. However, nephro, hepato, neuro cardio, and hematological toxicities associated with ifosfamide render its use limited. These side effects could range from organ failure to life-threatening situations. The present study aimed to evaluate the attenuating efficiency of Berberis vulgaris root extract (BvRE), a potent nephroprotective, hepatoprotective, and lipid-lowering agent, against ifosfamide-induced toxicities. The study design comprised eight groups of Swiss albino rats to assess different dose regimes of BvRE and ifosfamide. Biochemical analysis of serum (serum albumin, blood urea nitrogen, creatinine, alanine transaminase, aspartate transaminase, alkaline phosphatase, lactate dehydrogenase, total cholesterol, and triglycerides) along with complete blood count was performed. Kidney, liver, brain, and heart tissue homogenates were used to find malondialdehyde, catalase, and glutathione S-transferase levels in addition to the acetylcholinesterase of brain tissue. The results were further validated with the help of the histopathology of the selected organs. HeLa cells were used to assess the effect of BvRE on ifosfamide cytotoxicity in MTT assay. The results revealed that pre- and post-treatment regimens of BvRE, as well as the combination therapy exhibited marked protective effects against ifosfamide-induced nephro, hepato, neuro, and cardiotoxicity. Moreover, ifosfamide depicted a synergistic in vitro cytotoxic effect on HeLa cells in the presence of BvRE. These results corroborate that the combination therapy of ifosfamide with BvRE in cancer treatment can potentiate the anticancer effects of ifosfamide along with the amelioration of its conspicuous side effects.